Relationship of the Compliance Level of Antihypertensive Drug Use in First and Advanced Level Health Facilities - Rizal Rizal (Jurnal Sains dan Kesehatan, 2021)
The adherence with therapy in hypertensive patients is important to note because hypertension is a disease that cannot be cured but can only be controlled. The success of controlling blood pressure in hypertensive patients influenced by compliance factors in taking antihypertensive drugs. The purpose of this study is to evaluate the relationship between the level of adherence of antihypertensive drugsuse in first and advanced health facilities. The study design was an observational cross sectional using subjects with hypertension patients older than or equal to 18 years old at Kotabunan Bolaang Mongondow Health Center (first level health facility) and outpatient installation of Robert Wolter Monginsidi Hospital in Manado (advanced health facilities) during the period from October to December 2019. The level of compliance with the use of antihypertensive drugs was assessed using the MMAS-8 questionnaire (Morisky 8-Item Medication Adherence Scale). The total patients in this study were 171 patients, as many as 73 patients in the first level health facilities and 98 patients in the advanced health facilities. The data of patient adherence in the use of antihypertensive drugs in the first level of health facilities showed 83.56% with low levels of adherence (MMAS score <6), and only 16.44% with moderate to high levels of adherence (MMAS score 6-8). In the advanced level of health facilities were 85.71% of patients with low adherence and 14.29% with moderate to high adherence. Comparative statistical of adherence on the two health facilities was not significantly different, with p = 0.767 (95% confidence interval). The data shows that the average patient has a routine history of control as much as 91.8% in health facilities. Based on these results, recommended that each hospital and health center must require its pharmacists to do pharmaceutical practices, and each pharmacy must not provide drug services without the presence of a pharmacist.